Analysis of rate, types and causes of uveitis in children hospitalized at Ophthalmology Clinic in Wroclaw in years 2001-2006 - Iwanejko, Małgorzata; Turno-Kręcicka, Anna; Barć, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: The aim of the paper was to analyse frequency, causes and type of uveitis at children hospitalized in Ophthalmology Clinic of Medical Academy in Wrocław in years 2001-2006. Materials and methods: Material from 64 (88 pairs) children’s eyes was analyzed. There were 35 (54.7%) girls and 29 (45.3%) boys admitted to the Clinic with suspicion of uveitis. Results: There were 17 (26.6%) children with uveitis anterior, 15 (23.4%) with pars planitis and 32 (50.0%) with uveitis posterior. The uveitis occurred in both eyes in 33.9%. Aetiology of uveitis was recognized at 30 (46.9%) patients, at 12 (16.6%) cases uveitis was related to systemic disease. At 22 (34.4%) ill children recognition of aetiology was not possible. The most often cause of uveitis anterior was juvenile chronic arthrosis inflammation and it occurred at 8 (47.1%) children – 5 girls, and 3 boys. For the most patients 12 (80.0%), in case of pars planitis recognition of aetiology was impossible. Toxoplasmosis was the most often cause for uveitis posterior and it occurred at 14 (43.8%) children. Conclusions: Parasitic background is still considerable cause of uveitis among children. Juvenile chronic arthritis is the most often cause for uveitis anterior. In considerable amount of children cases, recognition of aetiology of uveitis was not possible.